Academic freedom and educational responsibility in malaysian higher institutions of learning - Hashim, Che Noraini; Syed Azman, Syed Marwan Mujahid; Syed Azman, Sharifah Nur Asmaa’ (IIUM Press, 2014)
New challenges of academic freedom and educational responsibility in Malaysian higher institutions of learning had been of great concern to all parties alike. However, academic freedom needs to be accompanied by educational responsibility. In Malaysia, serious research regarding academic freedom and academic responsibility, is yet to be undertaken. This paper identifies the relationship between academic freedom and educational responsibility; highlights major challenges faced by academicians in exercising academic freedom, and analyses responses from academicians. In addition, the paper suggests some improvements to the current practices of academic freedom in Malaysian higher institutions of learning. A semi-structured interview schedule was designed to gain insight on academic freedom and educational responsibility from randomly selected senior academicians attached to three Malaysian universities. Findings show that there exists a strong positive relationship between academic freedom and educational responsibility. Respondents also perceived that the regulations and restrictions imposed upon academicians did not act as obstacles to voice opinions, if the regulations and restrictions were taken positively and are used as measures to exercise academic responsibility. Their perceptions suggest that the main challenge faced by academicians comes, perhaps, from their own fears and inhibitions. The prognosis is that academic freedom in Malaysian universities can be realized by students and academicians alike, if they express their views within certain limitations; but the society and the government should be more tolerant and be receptive to constructive criticism.